PENGARUH PAPARAN SABUN MANDI CAIR NON ANTISEPTIK PADA BERCAK DARAH TERHADAP KRISTAL HEMOGLOBIN DENGAN TES TEICHMANN DAN TES TAKAYAMA - Hilda Fauziah Lainatus Shifa; Enikarmila Asni; Mohammad Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTThe purpose of crime scene investigation is to gather evidence, such as blood, that can give information about chronology of events in crime scene. One of forensic examination of blood is confirmatory test (Teichmann test and Takayama test) that can confirm if suspected object is blood. The criminals can wipe out blood using non antiseptic liquid bath soap. The aim of this study was to know effect of non antiseptic liquid bath soap exposure on bloodstains to hemoglobin crystal with Teichmann test and Takayama test. The design of this study was pre test and post test experimental. This study was conducted in Biochemical Laboratory of Medical Faculty of Riau University. Samples of this study were 50 bloodstain slides (2 control slides and 48 slides that have been exposed with 12 kind of non antiseptic liquid bath soap). The result of this study was 48 bloodstain slides (100%) had positive result with Teichmann test and Takayama test and crystal’s shape was same as crystal’s shape on control slides. The effect of non antiseptic liquid bath soap exposure on bloodstains to hemoglobin crystal with Teichmann test and Takayama test could not be determined because statistical analysis could not be done.Keywords : bloodstain, hemoglobin crystal, non antiseptic liquid bath soap, Teichmann test,Takayama testPENDAHULUANPemeriksaan tempat kejadian perkara (TKP) bertujuan untuk mengumpulkan barang-barang bukti yang dapat memberikan informasi tentang kejadian di TKP, salah satunya adalah cairan tubuh manusia. Cairan tubuh yang sering ditemukan di TKP adalah darah. Darah dapat ditemukan pada kasus kekerasan fisik, seperti pembunuhan, penganiayaan, pemerkosaan, dan kecelakaan.1Deteksi dan identifikasi darah di